The Sovereign Immunity Entitlement of Sunken Foreign Military Wreck Within Indonesian Territorial Water: Hak Kekebalan Kedaulatan atas Bangkai Kapal Militer Asing yang Tenggelam di Wilayah Perairan Indonesia - Wati, Erna; Pribadi , Insan; Iriyani, Meiske (Perspektif Hukum, 2025)
The 2014 retrieval of two Dutch warship wrecks from Indonesian waters, remnants of World War II's Battle of Java, sparked legal debate regarding sovereign immunity for sunken warships. The wrecks' disappearance, revealed during a 75th-anniversary commemoration, questions the continued applicability of such immunity in foreign waters. This study examines the wrecks' legal status, particularly their exclusion from the 2001 UNESCO Convention due to their age. Employing juridical-normative research, the study analyses international legal instruments, court decisions, literature, and state practices. Findings suggest that while sovereign immunity persists, its scope is limited. A non-operational wreck serves no military purpose but maintain its identity. The absence of a comprehensive international framework underscores the importance of the Indonesia-Netherlands bilateral agreement in protecting remaining wrecks. The study concludes that increased international cooperation is crucial for addressing legal uncertainties surrounding sovereign wrecks and ensuring their preservation.